Use of Exogenous Enzymes on Laying Hens Feeding During the Second Production Cycle - Costa, Fernando Guilherme Perazzo; Oliveira, C.F.S.; Goulart, C.C.; Figueiredo, D.F.; Neto, R.C.L. (International Journal of Poultry Science, 2008)
The aim of this research was to evaluate the effect of exogenous enzymes on performance and egg quality of second production cycle laying hens. One hundred and sixty laying hens, 72 week-old, were used during five periods of 28 days each. Birds were distributed in a completely randomized design, with four treatments and five replicates, using eight birds per experimental unit. Treatments consisted in two diets enzyme-free (positive control (PC) and negative control (NC)) and two diets with exogenous enzymes addition (reformulated diet (RD) and “on top” diet (OT)). Feed consumption, egg weight and internal and external egg quality were not affected by treatments. Egg production (EP), egg mass (EM) and feed conversion by egg mass and egg dozen were worse when using NC. Exogenous enzymes addition (RD and OT) resulted in a performance similar or superior to PC diet for those variables and birds fed OT diet presented better results for EP and EM. There was no treatment effect on excreta humidity and tibial ashes and phosphorus. However, there was an effect due to enzymes supplementation on plasmatic calcium and phosphorus, with RD resulting in similar levels to PC and OT diet presenting higher levels, which indicate that the enzyme was efficient in turn those minerals available. Calcium tenor in tibia and bone resistance were altered by treatments, with lower values obtained in birds that received “on top” enzymatic supplementation. Supplementation with Allzyme® SSF and Allzyme® VegproTM was efficient in increasing egg production in second production cycle laying hens.